Legal Analysis of Marketing Using Photos of Other People's Products Perspective of Fatwa Number 1 Of 2005 Concerning Protection of Intellectual Property Rights (Shopee Case Study) - Dinda Febrianti Santoso; Tetty Marlina Tarigan (Warmadewa Press, 2024)
This study aims to analyze the legality of marketing using photos of products owned by others from the perspective of MUI Fatwa No. 1 of 2005 on Intellectual Property Rights Protection. The focus is on marketing activities conducted on the Shopee e-commerce platform. The research involves observing several seller accounts on Shopee that use photos of other sellers' products without permission. This practice raises questions about its validity according to Islamic law as regulated by the fatwa related to intellectual property rights. To achieve this objective, the author employed a conceptual approach and field case studies. The results indicate that marketing using other people's product photos without permission violates the principles of intellectual property rights protection as stipulated in MUI Fatwa No. 1 of 2005. Although such practices may be considered valid in terms of the transaction, they fall into the category of fasid (defective) sales, and the perpetrators are deemed sinful.